Development of Global Chemical Profiling for Quality Assessment of Ganoderma Species by ChemPattern Software - Hui Zhang; Huijie Jiang; Xiaojing Zhang; Shengqiang Tong; Jizhong Yan (Journal of Analytical Methods in Chemistry)
Triterpenoids are the major secondary metabolites and active substances in Ganoderma, considered as the “marker compounds” for the chemical evaluation or standardization of Ganoderma. A response surface methodology was used to optimize the ultrasonic-assisted extraction of triterpenoids. The extraction rate was 7.338 ± 0.150 mg/g under the optimum conditions: 87% ethanol, ratio of solid to liquid (w : v) 1 : 28, and ultrasound extraction time 36 min. Based on the high sensitivity and selectivity of HPLC-LTQ-Orbitrap-MSn, 24 components of triterpenoids were tentatively identified in the negative mode. Then, the global chemical profiling consisting of HPLC and TLC fingerprints generated by ChemPattern™ software was developed for evaluation of Ganoderma species. For fingerprint analysis, 11 peaks of triterpenoids were selected as the characteristic peaks to evaluate the similarities of different samples. The correlation coefficients of similarity were greater than 0.830. The cluster analysis showed a clear separation of three groups, and 11 peaks played key roles in differentiating these samples. The developed global chemical profiling method could be applied for rapid evaluation, quality control, and authenticity identification of Ganoderma and other herbal medicines.